SUARA SHOLAWAT SIMTUBDHURAR TERHADAP RESPIRASI, DENYUT JANTUNG DAN SATURASI OKSIGEN PADA NEONATUS BBLR - Arsyad, Muhammad; Santi, Eka; Damayanti, Emmelia Astika F. (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
LBW neonates have a proportion of 20% of all infant birth rates in the world and oftenexperience stress that is manifested by increased heart rate and respiration and decreased oxygensaturation. Stimulation therapy is needed that can support growth and development. Soundtherapy can provide peace for the neonate, so far there is no known sound effect of sholawat forLBW neonates. This study aims to look at the sound effect of sholawat on heart rate, respirationand oxygen saturation in LBW neonates. The research method using Pre Experimental OneGroup Pre-Post Test Design was carried out on 15 infants treated at the NICU and usedpurposive sampling technique from October to December 2018. The instruments used by MP3scontaining the sound were Simtubdhurar prayer 40 minutes of playing through speakers withmaximum sound get to the subject of 60 decibels measured by a sound level meter. The meanheart rate and respiration after receiving treatment showed a decrease and increase in oxygensaturation. There was a significant decrease in pulse (Sig. (2-tailed)= 0.001) and respiration(Asymp. Sig. (2-tailed)= 0.009) and increased oxygen saturation (Asymp. Sig. (2-tailed)= 0.004)on the third day of treatment. The sound of prayer has an influence on pulse, respiration andoxygen saturation in LBW neonates. Sholawat sounds can be a choice of complementarytherapies while undergoing treatment in the NICU room.